Development of iBeacon application 1 - Tan, Tricia Min (Nanyang Technological University, 2022)
iBeacon is a protocol developed by Apple and is transmitted through Bluetooth Low Energy (BLE) devices. It is typically used to transmit a universally unique identifier and short data information. Applications include indoor positioning, tracking objects or customers, push notification or advertisement, etc.